Correction: Spaceflight Activates Lipotoxic Pathways in Mouse Liver. - Karen R Jonscher; Alba Alfonso-Garcia; Jeffrey L Suhalim; David J Orlicky; Eric O Potma; Virginia L Ferguson; Mary L Bouxsein; Ted A Bateman; Louis S Stodieck; Moshe Levi; Jacob E Friedman; Daila S Gridley; et al. (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0152877.].